Laparoscopic Adnexectomy for Ovarian Torsion during Late Pregnancy: Case Report of a Non-Conservative Treatment and Literature Analysis - Bouquet de Joliniere, Jean (Front Surg, 2017)
Diagnosis of adnexial torsion is difficult during pregancy (1). The time of decision and laparoscopy is that of the risk of necrosis of the adnexa and, therefore, of the ovarian prognosis. The loss of an ovary can compromise the following fertility. Even if concerns related to laparoscopy in pregnant patients include a limited surgical field, with a risk of uterine injury and negative fetal effects of CO(2) insufflation. Evidence base suggests that minimally invasive surgery can be safe and better than laparotomy for management of adnexal masses during late pregnancy with good postoperative and obstetric outcomes. If for most authors laparoscopy appears to become the best approach for ovarian torsion during pregnancy (2), nonetheless, the ideal surgical laparoscopic approach of adnexa in late pregnancy remains controversial. Since there is no technical gold standard to overcome surgical difficulties which could make laparoscopic procedures as real challenge in patients in second and third trimester (3); at least, in case of radical and non-conservative treatment, the risk for a first trimester of pregnancy is to remove the corpus luteum (1).